2004
DOI: 10.1007/s00414-004-0445-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic identification of forensically important flesh flies (Diptera: Sarcophagidae)

Abstract: Unequivocal identification of fly specimens is an essential requirement in forensic entomology. However, not all species can be determined at every developmental stage, which is illustrated by the flesh flies (Diptera: Sarcophagidae), important members of the necrophagous insect fauna. Up to now no suitable key for the identification of the immature stages of this family of flies exists. DNA analysis of selected mitochondrial genes was applied to solve this problem. Sequence data of selected regions of the CO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
100
1
9

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(115 citation statements)
references
References 15 publications
5
100
1
9
Order By: Relevance
“…Divergences between genera of Sarcophagidae show an average pairwise divergence of 0.103. Divergence values among Peckia and Oxysarcodexia were 0.120 and within P. chrysostoma this value was 0.003 and for P. intermutans was 0.007; these values correspond to those found for other forensically important fly species (Wallman and Donellan, 2001;Zehner et al, 2004;Meiklejohn et al, 2011). **Data not available.…”
Section: Resultssupporting
confidence: 60%
“…Divergences between genera of Sarcophagidae show an average pairwise divergence of 0.103. Divergence values among Peckia and Oxysarcodexia were 0.120 and within P. chrysostoma this value was 0.003 and for P. intermutans was 0.007; these values correspond to those found for other forensically important fly species (Wallman and Donellan, 2001;Zehner et al, 2004;Meiklejohn et al, 2011). **Data not available.…”
Section: Resultssupporting
confidence: 60%
“…All the ten species were separated with high bootstrap support (50-100%) which showed the robustness of this gene to distinguish between Indian flesh flies. Zehner et al [40] investigated twelve species of Sarcophagidae and showed a bootstrap value of 52-90% in the NJ tree. Song et al [36] noted ≥94% bootstrap support which strongly supported monophyly of the three clades including the Parasarcophaga clade, Boettcherisca clade and the Liopygia clade and suggested interior relationship as S. albiceps, S. misera and S. sericea for the Parasarcophaga clade.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent to this research, mtDNA has been widely used for DNA analysis in forensic entomology, using COI and COII gene sequences analysis for distinguishing forensically important blow flies and flesh flies [4][5][6][7][8][9][10][11][12][13][14]. In purpose, such molecular work is similar to other non-entomological forensic methods in that it provides supplementary evidence in the form of PMI estimate to support the charge of a suspect to the crime.…”
Section: Simple Pcrmentioning
confidence: 99%